2016
DOI: 10.1016/j.anaerobe.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A MLST Clade 2 Clostridium difficile strain with a variant TcdB induces severe inflammatory and oxidative response associated with mucosal disruption

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…Specifically in Brazil, several studies in the last decade failed to detect RT027 and RT078 in humans (Balassiano et al, 2009;Balassiano et al, 2011;Monteiro et al, 2014;Silva et al, 2015;Cançado et al, 2018). Although these known hypervirulent ribotypes seems not frequent in our country, studies have identified several binary toxin (CDT) positive strains in humans and animals in Brazil, some from new ribotypes (Silva et al, 2015;Costa et al, 2016;Cançado et al, 2018). This finding is of concern once the production of binary toxin is frequently associated with hipervirulent strains (Rodriguez et al, 2016) and with increased lethality and recurrence (Berry et al, 2016).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Specifically in Brazil, several studies in the last decade failed to detect RT027 and RT078 in humans (Balassiano et al, 2009;Balassiano et al, 2011;Monteiro et al, 2014;Silva et al, 2015;Cançado et al, 2018). Although these known hypervirulent ribotypes seems not frequent in our country, studies have identified several binary toxin (CDT) positive strains in humans and animals in Brazil, some from new ribotypes (Silva et al, 2015;Costa et al, 2016;Cançado et al, 2018). This finding is of concern once the production of binary toxin is frequently associated with hipervirulent strains (Rodriguez et al, 2016) and with increased lethality and recurrence (Berry et al, 2016).…”
mentioning
confidence: 84%
“…The epidemiology of CDI is highly dynamic as new strains continue to emerge worldwide (Munoz et al, 2017). Considering both the geographical differences of CDI epidemiology and the potential worldwide spread of epidemic isolates, epidemiological studies to characterize currently circulating strains and permanent surveillance are necessary (Janezic, Rupnik, 2015;Costa et al, 2016). Despite this, circulating strains in Latin America countries are largely unknown (Balassiano et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, strain ICC45-ST41 produced weaker proinflammatory responses than 2811-ST41. Among multiple explanations, this difference could be tracked to the synthesis of a variant TcdB in the former [ 34 ]. However, information on the amount of secreted TcdA and CDT by strains from this ST is still lacking, though it could clarify the observed differences in proinflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“… a According to the database of the National Microbiology Laboratory of Canada b CPE, cytopathic effect; C, classic; V, variant [ 32 , 34 ] del 18 pb deletion in tcdC Ov Toxin overproduction [ 32 , 34 ] …”
Section: Methodsmentioning
confidence: 99%